Unconventional poultry feeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Maggots, toads, azolla and water hyacinth are just a few of the unconventional raw materials being considered for poultry feeds in the Philippines. Substituting these for expensive imported materials offers farmers the opportunity to cut their...